Determinants Of Audit Quality: Evidence From Indonesia - Endang Mardiati; Kristin Rosalina; Puteri Thea Avanti; Laila Fitriyah LH (Jurnal Akademi Akuntansi, 2022)
Corporate scandal in 2018 involving well-known public accounting firm in Indonesia is predicted to be caused by the quality of audits on financial statement that distort the decision-making process by users. Meanwhile, based on agency theory, agency problems between management as the preparer of financial statements and shareholders as users of these reports can be mitigated through the high quality of audit process. Therefore, the purpose of this study is to examine the factors that affect audit quality such as audit engagement tenure, public accounting firm's rotation and size, auditee size, as well as auditee economic sector. The population in this study are companies listed on the Indonesia Stock Exchange in 2015-2017. By using secondary data sources from audited financial statements and random sampling method in obtaining the data, a total of 438 companies during 3 years of observation were used in this study. The results show that tenure and the auditee size have a negative effect on audit quality. This information can be used as a consideration for professional bodies and regulators in formulating policies related to the limit of audit engagement period to maintain the quality of audit results. In addition, the auditee size can be used by the auditor as the main indicator of audit complexity which in turn implies the audit strategy formulation.